1982
DOI: 10.1159/000207030
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Characteristics of Ferritin in Human Bone Marrow

Abstract: It has been found possible to test ferritin concentrations in the reticulum and hemopoietic cells from human bone marrow by an immunoradiometric assay. Ferritin concentration in healthy test persons amounts to 0.92 ± 0.38 ng/μg protein in the reticulum and 0.084 ± 0.031 ng/μg protein in hemopoietic cells. In healthy test persons about 90% of the ferritin is localized in the reticulum and about 10% in the hemopoietic cells. The ferritin concentration in the reticulum is decreased in patients having iron deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1988
1988
1988
1988

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Ferritin is stored mainly in parenchymal liver cells and in the reticuloendothelial system [Mason et al, 1978]; it is also present in bone marrow erythroblasts [Oertel et al, 1982] and in circulating monocytes [Cragg et al, 1984;Ohnishi et al, 1985] and [3-lym phocytes [Cragg et al, 1984], In idiopathic hemo chromatosis, storage iron is accumulated preferen tially in parenchymal liver cells than in reticuloendo thelial cells [Ross et al, 1975]; the reverse is true of chronic diseases (inflammatory, neoplastic) causing an increase of serum ferritin [Torrance et al, 1980], Immunohistochemical assessment of ferritin has been performed, with good results, on normal tissues [Mason et al, 1978;Cohen et al, 1984 a;Zhou et al, 1987] and on tumors [Rossiello et al, 1984;Cohen et al, 1984 a, b;Imoto et al, 1985;Ishimatsu et al, 1987;Campo et al, 1987;Zhou et al, 1987], Zhou et al [1987] observed immunohistochemically demon strable ferritin in 75% of nonneoplastic livers and in 40 % of hepatocellular carcinomas; of 16 patients pos itive for ferritin in hepatocellular carcinoma cells, stainable iron was found in only 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferritin is stored mainly in parenchymal liver cells and in the reticuloendothelial system [Mason et al, 1978]; it is also present in bone marrow erythroblasts [Oertel et al, 1982] and in circulating monocytes [Cragg et al, 1984;Ohnishi et al, 1985] and [3-lym phocytes [Cragg et al, 1984], In idiopathic hemo chromatosis, storage iron is accumulated preferen tially in parenchymal liver cells than in reticuloendo thelial cells [Ross et al, 1975]; the reverse is true of chronic diseases (inflammatory, neoplastic) causing an increase of serum ferritin [Torrance et al, 1980], Immunohistochemical assessment of ferritin has been performed, with good results, on normal tissues [Mason et al, 1978;Cohen et al, 1984 a;Zhou et al, 1987] and on tumors [Rossiello et al, 1984;Cohen et al, 1984 a, b;Imoto et al, 1985;Ishimatsu et al, 1987;Campo et al, 1987;Zhou et al, 1987], Zhou et al [1987] observed immunohistochemically demon strable ferritin in 75% of nonneoplastic livers and in 40 % of hepatocellular carcinomas; of 16 patients pos itive for ferritin in hepatocellular carcinoma cells, stainable iron was found in only 2.…”
Section: Discussionmentioning
confidence: 99%
“…This does not seem a limitation, be cause only ferritin stored in reticuloendothelial cells is significant: indeed, the synthesis of ferritin by erythroblasts is scarcely influenced by iron, and may be a genome expression in the course of cellular dif ferentiation. Anyway, erythroblastic ferritin makes up only 10% of bone marrow ferritin [Oertel et al, 1982], and so its influence on quantitative evaluations is marginal.…”
Section: Discussionmentioning
confidence: 99%